STRESS ANALYSIS PADA HORIZONTAL AXIS WIND TURBINE BLADE BERBAHAN KAYU - Waluyo, Roy (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2018)
The blade turbine is a component that experiences a very high stress on a wind turbine. Materialsoften used are aluminum composite, polymer and even steel. Aluminum has a high fatigue. Plasticis very suitable But it requires mold while steel has a great weight. Wood is an alternative materialfor a blade turbine. Because it is lightweight, strong, easily shaped, and has high fatique resistanceand is easy to obtain. In this research, a stress analysis on a blade with balsa wood material withfixed force 5 Newton is applied. The result of analysis by using Autodesk Inventor student version,shows that the minimum Stress that occurs is: 12.1265 N / m ^ 2 and the maximum stress is:955595 N / m ^ 2. The maximum stress occurs at the point / node 390 or the area near theassembly hub or fixed geometry marked in red.